1997
DOI: 10.1111/j.1528-1157.1997.tb01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Effects of Tiagabine, a Selective GABA Uptake Inhibitor, in the Rat Kindling Model of Temporal Lobe Epilepsy

Abstract: Summary: Purpose:We determined the antiepileptic profile of tiagabine (TGB), a selective y-aminobutyric acid (GABA) uptake inhibitor, in the rat kindling model of temporal lobe epilepsy (TLE).Methods: The anticonvulsant and adverse effects of TGB were examined in amygdala-or hippocampal-kindled rats and compared with those of other GABA uptake inhibitors (SKF89976A and NNC-7 1 1) and conventional antiepileptic drugs [AEDs: valproate (VPA) and carbamazepine (CBZ)]. In addition, the antiepileptogenic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…The severity and duration of convulsions in amygdala-kindled rats are reduced (4); in addition, daily treatment with TGB 10 mgkg for 10 days significantly retards the development of kindling (7). TGB also shows activity in maximal electroshockinduced seizures, bicuculline-induced seizures in rats (4), and picrotoxin-induced convulsions in mice (8).…”
Section: Animal Studies and Pharmacokineticsmentioning
confidence: 99%
“…The severity and duration of convulsions in amygdala-kindled rats are reduced (4); in addition, daily treatment with TGB 10 mgkg for 10 days significantly retards the development of kindling (7). TGB also shows activity in maximal electroshockinduced seizures, bicuculline-induced seizures in rats (4), and picrotoxin-induced convulsions in mice (8).…”
Section: Animal Studies and Pharmacokineticsmentioning
confidence: 99%
“…and 2.5 mg/kg, i.p., respectively. 18,19) NNC-711 and diazepam also inhibited pentetrazol-induced kindled seizure activities in mice at doses of 2 mg/kg, i.p. and 1 mg/kg, i.p., respectively; however, significant potentiation of effects of both drugs were observed in simultaneous use with AIDA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been used as a mood stabilizer and in treatment of panic disorder. Tiagabine has exhibited antikindling and antianxiety effects in preclinical studies [82,83], and its anxiolytic effects have been shown across anxiety disorders [84,85•]. Tiagabine is well tolerated and may hold promise in treating PTSD via its facilitation of GABA neurotransmission [23,86,87].…”
Section: Tiagabinementioning
confidence: 99%